Impact pathways of personality and psychosocial stress on depression among adult community residents in China: a fuzzy-set qualitative comparative analysis - Yang, Xi; Yu, Liuruyu; Zhang, Shengming; Wei, Zhaoguo; Xie, Gaoqiang; Wang, Jianhong (Frontiers in Psychology, 2024)
Objective: Depression is the common mental illness with high incidence, which is one of the greatest contributors to the global burden of diseases. Various factors are associated with depression and the working mode is complex. Instead of studying single-factor effects, this study aimed to explore the combination of high-risk factor sets for depression among adult community residents.We conducted a cross-sectional survey in Shenzhen, China from January 2021 to March 2021. A simple sampling method was used to enrolled participants. A total of 1965 adult residents completed the survey and were tested using the Patient Health Questionnaire-9 (PHQ-9), Eysenck personality Questionnaire-revised Short Scale for Chinese(EPQ-RSC), Questionnaires of psychosocial stress survey for groups (PSSG). The fs-QCA method was used to explore the high-risk factor sets for depression among adult community residents.The prevalence of depression among adult residents in Shenzhen, China was 6.36%. The mean scores of PHQ-9 were higher among women and single residents.The combination of low extroversion(e)-high neuroticism(N) in personality trait, combined with high life event(V)-high negative emotional responses to events(G)high positive emotional responses to events(O)-high positive coping styles to events(I) (e*N*V*G*O*I) was high-risk factor sets for depression. The overall consistency was 0.843, and the overall coverage was 0.330.Our study suggested that together with the personality traits including neuroticism and introversion, stressful life events could be the crucial incentive factors regardless of coping strategies was used by adult community residents. This study provides data for developing comprehensive interventions such as regulating neuroticism and introversion levels, and reduce stressors in adult community residents could help preventing depression.